2019
DOI: 10.1080/00218464.2019.1667776
|View full text |Cite
|
Sign up to set email alerts
|

J-integral analysis of the mixed-mode fracture behaviour of composite bonded joints

Abstract: The adhesive technology has been constantly growing and expanding into industrial environments, not only for traditional applications but also for high-end applications, where it has been competing fairly with the conventional connection technologies, such as welding, brazing, bolting and riveting. Its unique key features allow it to raise the type of technology to unreachable levels, for certain applications, by its competitors. Some of the advantages are the lightness of the adhesively-bonded joints, good be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The data points of da Silva are offset to the other methods. Former works [36][37][38] using the SLB test resulted in α = 0.5 for the AV138 and α between 0.5 and 1 for the 2015, which was positively validated by CZM modelling. Thus, in this work, the numerical part that follows will clarify the found differences.…”
Section: R-curvesmentioning
confidence: 68%
“…The data points of da Silva are offset to the other methods. Former works [36][37][38] using the SLB test resulted in α = 0.5 for the AV138 and α between 0.5 and 1 for the 2015, which was positively validated by CZM modelling. Thus, in this work, the numerical part that follows will clarify the found differences.…”
Section: R-curvesmentioning
confidence: 68%
“…Then, it was found that the chosen composite was a suitable alternative to conventional thermoset composites. Similarly, SLB for adhesive joints were modelled by Santos and Campilho [17] and Loureiro et al [18]. In both cases, the numerical models reproduced the experimental setup performed by the authors.…”
Section: Introductionmentioning
confidence: 80%
“…The procedure in this work involved using an optical method founded on taking high-resolution pictures during the tests (Figure 3), and then performing a vector and geometric analysis of the images captured during the tests by imaging software to produce a value of θ p , δ n , and δ s for each picture, which can be correlated with the testing machine data. More details about this procedure and geometrical extraction of the parameters from the pictures can be found in previous work [18].…”
Section: J-integral Formulationmentioning
confidence: 99%
See 2 more Smart Citations